The adaptive boundary approach for exposure assessment in a broadband EMF monitoring. (November 2016) - Kljajic, Dragan; Djuric, Nikola
Highlights: A new approach for exposure assessment to EMF was proposed, regarding broadband measurement. Approach suggests calculation of daily exposure boundaries, using results of broadband continuous monitoring. Advancement of the proposed approach is described, by adaptation of the exposure boundaries. The frequency scanning was used to adapt new boundaries, increasing precision of the assessment. Test measurement shows that reduction in boundaries difference of 36.25% can be obtained. Abstract: The boundary approach for the assessment of daily exposure to electromagnetic fields (EMF) has been recently proposed for the continuous and broadband EMF monitoring of the Serbian Electromagnetic Field Monitoring Network – SEMONT. This approach is based on the determination of the daily upper and lower exposure boundaries, combining data of the continuous in situ EMF monitoring in a broadband frequency range and the minimal and maximal prescribed reference levels. The real exposure is positioned between these boundaries. In this paper, the enhancement of the boundary approach is presented. By adjusting the existing boundaries and reducing the difference between them, the precision of the daily exposure assessment in the SEMONT system has been improved. The frequency selective measurement has been used to determine the frequencies on which EMF sources radiate over a particular area and in situ location. Consequently, the new minimal and maximal reference levels can be selected; these are suitable for a particular in situ location and should be used for the calculation of exposure boundaries on that location. A simple in situ test measurement of the high-frequency electric field strength was performed, in order to verify the proposed adaptive boundary approach. The analysis shows that this approach attained reduction in boundaries difference of 36.25%, regarding the Serbian legislation, resulting with the increased precision of the daily exposure assessment for the broadband EMF monitoring.